2013
DOI: 10.1136/bmjopen-2013-002586
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis-associated mortality in England: an analysis of multiple cause of death data from 2001 to 2010

Abstract: ObjectivesTo quantify mortality associated with sepsis in the whole population of England.DesignDescriptive statistics of multiple cause of death data.SettingEngland between 2001 and 2010.ParticipantsAll people whose death was registered in England between 2001 and 2010 and whose certificate contained a sepsis-associated International Classification of Diseases, 10th Revision (ICD-10) code.Data sourcesMultiple cause of death data extracted from Office for National Statistics mortality database.Statistical meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(74 citation statements)
references
References 19 publications
2
68
0
4
Order By: Relevance
“…5 Only 7.0% of deaths definitely associated with sepsis did not occur in hospital. 5 Incidence of sepsis is particularly high in patients who are admitted to ICUs. A large retrospective analysis of 56,673 admissions of adult patients to ICUs in England Wales and Northern Ireland, between 1995 and 2000, found that 27.1% met the criteria for severe sepsis with the first 24 hours of admission.…”
Section: Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Only 7.0% of deaths definitely associated with sepsis did not occur in hospital. 5 Incidence of sepsis is particularly high in patients who are admitted to ICUs. A large retrospective analysis of 56,673 admissions of adult patients to ICUs in England Wales and Northern Ireland, between 1995 and 2000, found that 27.1% met the criteria for severe sepsis with the first 24 hours of admission.…”
Section: Populationmentioning
confidence: 99%
“…4 In addition, a recently published analysis of the 2001-10 Office for National Statistics (ONS) mortality data found that, during this period, 4.7% of all deaths recorded in England were 'definitely directly associated with sepsis'. 5 Ninety-nine per cent of deaths definitely associated with sepsis had at least one of the ICD-10 codes -A40 (sepsis due to pneumonia), A41 (other sepsis) or P36 (sepsis of newborn due to streptococcus group B) -on the death certificate; however, only 8.6% of deaths definitely associated with sepsis in 2010 had a sepsis-related condition as the underlying cause of death. 5 Only 7.0% of deaths definitely associated with sepsis did not occur in hospital.…”
Section: Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the kidney function of inpatients is monitored more closely, partly due to the increase in AKI risk factors once admitted to hospital, such as the greater rate of sepsis [7]. Given this closer monitoring and the greater prevalence of AKI amongst inpatients [8], algorithms have been developed that can accurately identify AKI within this population in real-time [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…According to the present criteria many of them are regarded as sepsis.The results of the analysis of mortality in England for the period of 2001 2010 showed that 5.1% of deaths in the country were associated with sepsis [1], which is one of the most serious health problems according to the authors. In the United States sepsis is on the 11th position [2] in the list of the most frequent causes of death.…”
mentioning
confidence: 99%